School-based sexual and reproductive health education among adolescents in developing countries - Utami, Dyah Rahmawatie Ratna Budi; Nurwati, Ida; Lestari, Anik (International Journal of Public Health Science (IJPHS), 2024)
The increase in risky sexual behavior among adolescents indicates the need to strengthen sexual and reproductive health. Schools have an essential role, but few studies are related to mapping models of school-based sex and reproductive education for adolescents in developing countries. This scoping review examines school-based sexual and reproductive health education among adolescents in developing countries. A systematic approach was used to search the literature through 5 electronic databases: Science Direct, EBSCO, PubMed, CrossReff, and Proquest. Subsequently, two reviewers conducted a conformity analysis with the inclusion/exclusion criteria, and then the search results that met the requirements were analyzed descriptively. A total of 14 articles met the inclusion criteria. The model of sexual health education in schools comprises digital-based education, peer groups, and comprehensive sex education to improve life skills. Barriers to implementation include culture, traditional norms, organization, commitment, and supporting resources. The supporting factors are student enthusiasm, exciting methods and media, community, and parental support. School-based sexual and reproductive education increases knowledge and attitudes about sexual health. Therefore, there is a need for a comprehensive sexual education model integrated into the school curriculum using attractive media and involving several well-organized stakeholders.